Pojok Gizi di Festival Buah Provinsi Jawa Tengah 2020 - Mellia Harumi; Meiliana Meiliana (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
The Nutrition Corner as a community service program of Food Technology Department, Soegijapranata Catholic University conducted in the Fruit Festival of Central Java Province aimed to provide knowledge and advise about healthy food and balance nutrition guidance. The method included weight and height measurement as well as nutrition consultation. Through this activity, visitors were expected to understand the benefit of balance nutrition in daily meals and increase self-efficacy in choosing healthy food on maintaining good health.